Parallelization of Horner Method: Implementation Strategy and Error Analysis - Policarpo Abascal Fuentes; David García Quintas; Jorge Jiménez Meana; Antonio Palacio Muñiz (Research Updates in Mathematics and Computer Science Vol. 9, 2024)
Minimizing the computational cost of polynomial evaluation is a main problem in Computational Science. We present a modification of Horner’s method to exploit its advantages in the evaluation of sparse polynomials. We also propose a polynomial partitioning that allows to perform Horner’s method in parallel. In addition, we provide an analysis of the numerical error between the proposed parallel method and the classic algorithm.